Perlmutter revisited: Revealing the anomic mindset - Bohas, Alexandre; Morley, Michael J.; Kinra, Aseem (Journal of International Business Studies, 2021)
The assortment of issues that arise in situations where there is a divergence between managers’ prevailing mindsets and the demands of their complex operating environment have yet to be fully revealed. Engaging critically with Perlmutter’s framework and the broader global mindset literature, and drawing on insights curated from a 2-year field study, we reveal the existence of the anomic mindset among a cohort of international managers. We conceptualize this mindset as a stock of knowledge, cognitive and psychological attributes that results in these managers returning to and entrenching themselves in an outdated, most probably idealized, world view of business in opposition to a changing socio-economic context. Its presence sees them resisting rather than adapting to the globalization that surrounds them, and leads them to engage in detours from the pathway toward the development of a global mindset. Unlike the ethnocentric mindset which describes ex ante managerial thinking in organizations moving toward internationalization, the anomic mindset results from the ex post responses of managers following a protracted period of involvement in international business. Its existence opens up a significant debate on progress in, and the prospects for, globalization and the development of global mindsets, along with their preservation in the face of this persistent anomie.